TRANSFORMASI STRATEGI RUMAH SAKIT UNTUK MENINGKATKAN PASIEN EKSEKUTIF DI ERA DOMINASI BPJS: TINJAUAN ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI - Mulyadi Muchtiar; Isniar Budiarti; Siti Kurnia Rahayu; Dedi Sulistiyo (Media Riset Bisnis Manajemen Akuntansi, 2026)
The expansion of the National Health Insurance (JKN), administered by BPJS Kesehatan, has made BPJS patients the dominant users of hospital services, while financial margins from INA‑CBGs tariffs remain limited for hospitals that are not yet efficient. A qualitative case study was conducted at XYZ Hospital Jakarta, a private hospital serving BPJS and executive patients. Data were collected through document review, in-depth interviews with leaders and key health professionals, and observation of service flows in regular BPJS and executive polyclinics. Thematic analysis with the three philosophical lenses explored how segments are defined and positioned (ontological), what evidence informs strategic decisions (epistemological), and which values/Sharia considerations guide transformation (axiological).The findings indicate that the hospital views itself as operating in a “dual‑speed” healthcare market: a BPJS segment oriented to volume and efficiency and an executive segment oriented to added value, both bound to the same clinical quality standards.  The study concludes that strengthening the executive segment can be scientifically and ethically justified if designed as a transparent, evidence‑based dual‑speed model that ensures fairness and aligns with Islamic values.Keywords: hospital strategy, executive patients, BPJS, dual‑speed, philosophy of science.